Navigating the Paradigm Shift in Chronic Lymphocytic Leukemia Treatment from Chemotherapy to Targeted Therapies (Actualité hématologique au Canada, 2024)
The shift from traditional chemotherapy to more targeted therapies has been a landmark change in chronic lymphocytic leukemia (CLL) treatment. This transformation has implications for treatment efficacy, tolerability, and patient quality of life, along with implications for the Canadian oncology community at large, which must rapidly adapt to these advancements. This rapid development underscores the importance of continued responsiveness in medical practice, including more collaborative work with Canadian institutions and provincial cancer care to deliver these transformative therapies to patients. This review aims to offer practical guidance, from a Canadian perspective, for clinicians in treatment selection in the era of targeted therapies.